Malaysia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
This report provides the analysis of IMF's projections and estimates for Malaysia on gross domestic product by expenditures and production at constant prices; industrial production index; labor market developments; composition of investment and saving in current prices; consumer price index and producer price index; federal government revenues and grants; economic and functional classification of federal government expenditure and net lending; federal government operations and fiscal operations, operations of statutory bodies, state, and local governments; general government operations; monetary survey; banking survey; balance of payments; international reserves during 1995-99; interbank swap transactions, 1995-2000, and so on.